Ultrafast third-order nonlinear optical response of charge coupled gold nanoparticle-Ge24Se76 heterostructure - Vinod Kumar; Rituraj Sharma; Abhishek Bhatt; I. Csarnovics; Petr Nemec; H. Jain; K.V. Adarsh (Journal of Non-Crystalline Solids: X, 2023)
The donor-acceptor interaction of a charge-coupled heterostructure encompassing a metal and an amorphous semiconductor subjected to a laser field has many potential applications in the realm of nonlinear optics. In this work, we fabricate an electron donor gold nanoparticle (AuNP) and acceptor amorphous Ge24Se76 heterostructure on a quartz substrate using a sequential thermal evaporation technique. In this charge coupled heterostructure, we demonstrate the ultrafast third-order nonlinear absorptive and refractive response, and their sign reversal compared to pristine Ge24Se76. Enhanced optical nonlinearity in these heterostructures of varying plasmonic wavelengths is due to charge transfer, verified by the Raman spectroscopy. Further, the ultrafast transient absorption measurements support the thesis of charge transfer in the AuNP/Ge24Se76 heterostructure. These findings open up exciting opportunities for developing novel device technologies with far-reaching applications in nonlinear optics.